A Critical Review of Lignocellulosic Waste Pretreatment for Biofuel Production (International Journal of Innovative Research in Computer Science & Technology, 2021)
Environmental protection is a top priority,  and this can only be accomplished by minimizing  Chemicals are used in the manufacturing of fuel. As a  biofuel source, bioethanol production waste has become  more and more attractive. Using a proper pretreatment  technique, it may be transformed into a useful form for  biofuel generation. Researchers have employed a variety of  pretreatment techniques, including physical, chemical,  physicochemical, biological, and combination  pretreatments. Because a significant quantity of chemicals  are required to pretreat the lignocellulosic substrate,  chemical pretreatment is clearly more costly. Combination  pretreatments have been proven to be more successful than  solo pretreatments, and there is a wide range of  combinations that may be used in the future. A recent study  critically examines and analyzes various pretreatment  techniques, biomass supplies, chemical makeup of various  agricultural biomass, and its application for bioenergy  production. Various bioHydrogen, bioMethane, bioEthanol,  bioMethanol, bioButanol, and bioDiesel pretreatment  methods are also addressed.
Keywords: Bio-butanol; Bio-ethanol; Bio-hydrogen; Bio-methanol; Lignocellulosic materials